Republic of Lithuania : 2017 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that the economy of Lithuania has been gathering momentum, following sluggish performance in 2015 and most of 2016. Real GDP expanded by 3.9 percent in the first quarter of 2017 after rising by 2.3 percent in 2016. Strong private consumption, on the back of robust wage growth and low inflation that supported purchasing power, has long been a main driver of growth. Building on recent momentum, economic growth should be strong in 2017, rising to 3.2 percent. Improving external conditions and a turnaround in European funds absorption, as well as high capacity utilization, should spur exports and investment.